Assessment Awareness of Breast Cancer Signs, Risk Factors, and Barriers: An Online Cross‑Sectional Study in Syria - Bohsas, Haidara; Swed, Sarya; Alibrahim, Hidar; Sawaf, Bisher; Elsayed, Mohamed (International Journal of Medical Students, 2023)
Background: According to the World Health Organization (WHO), breast cancer (BC) is women’s most common type of cancer. In LAMICs, breast cancer incidence is low. However, a lack of information about the signs and symptoms of breast cancer potentially results in the disease’s progression to life-threatening stages.This study aimed to determine the levels of breast cancer symptom awareness among Syrian women and to identify the variables associated with a high level of awareness. Methods: From 3 September 2022 to 27 September 2022, Syrian women participated in an online cross-sectional survey to measure their knowledge about breast cancer, risk factors, and symptoms. This survey was derived from previous research that included a comprehensive, authorized scale. The admission requirement was 18-year-old or older Syrian women from all Syrian governorates. The questionnaire was divided into two portions; the first component included sociodemographic characteristics. Based on the original BCAM scale, the second portion assessed the participant’s knowledge of breast cancer symptoms, risk factors, and obstacles. Using the IBM SPSS V. 28.0 software, descriptive and multivariate logistic regression analyses were performed on the data. Results: Among 1305 study participants, the mean age and standard deviation of the individuals were 30.7 and 11.2, respectively. Students constituted almost three-quarters (75.2%) of the study respondents. The average level of knowledge about risk factors was higher among women with chronic diseases (Mean = 4.44, SD = 2.176), whereas jobless people had a higher average level of information regarding obstacles than other subgroups of practical circumstances. In addition, single women scored higher on the barrier comprehension scale than other marital status groups (mean=3.34, SD=2.32). Only two variables, including age and educational level, were statistically significant in predicting an acceptable degree of knowledge of the risk factors for breast cancer. Participants with a PhD were more aware than other educational subgroups (P-value 0.05; OR =6.186). Participants with a PhD. are projected to be 6.18 times more aware of breast cancer risk factors than those with lower levels of education. Women with chronic conditions were 1.84 times more likely than others to be aware of breast cancer barriers. Conclusion: Our findings indicate that Syrian females have a poor to moderate knowledge of breast cancer symptoms, risk factors, and barriers. It is proposed that more breast cancer awareness campaigns be conducted and that yearly screening programs be improved to combat the late detection of this illness. Social media and television might be effective venues for raising awareness of breast self-examination and early identification of symptoms.